1960
DOI: 10.1002/bjs.18004820829
|View full text |Cite
|
Sign up to set email alerts
|

Obstruction of popliteal artery by synovial cyst report of a case

Abstract: months he was reduced by pain to cease walking after zoo yards on the flat. Medical treatment gave no results, and surgery was sought in September, 1959. He had worked as a plasterer from 1945 to 1956, and again during the second half of 1958 for six months. In the latter period, almost up to the onset of the pain, he had worked on floors, kneeling on his right knee. The same applied to about 25 per cent of his time in the I r-year period. Since the pain he had driven a small truck around a timber yard.He was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
1
2

Year Published

1967
1967
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 1 publication
2
11
1
2
Order By: Relevance
“…It has also been described as a dilatation of the artery (Simon, 1963) as yellowish brown in colour (Ishikawa et al, 1961) and as a pulsatile lump (Lambley, 1963 ;Tytgat, Derom, and Galinsky, 1958). Dense periarterial adhesions similar to those found in Case 2 have been reported by other authors (Hiertonn et al, 1957;Robb, 1960;Tytgat et al, 1958;Ishikawa et al, 1961Bliss et al, 1963.…”
Section: Discussionsupporting
confidence: 86%
“…It has also been described as a dilatation of the artery (Simon, 1963) as yellowish brown in colour (Ishikawa et al, 1961) and as a pulsatile lump (Lambley, 1963 ;Tytgat, Derom, and Galinsky, 1958). Dense periarterial adhesions similar to those found in Case 2 have been reported by other authors (Hiertonn et al, 1957;Robb, 1960;Tytgat et al, 1958;Ishikawa et al, 1961Bliss et al, 1963.…”
Section: Discussionsupporting
confidence: 86%
“…In rare instances in which the popliteal artery is compressed by the Baker cyst in a pulsatile fashion, the patient can experience lower extremity claudication due to intermittent ischemia to the limb. [21][22][23][24][25] The popliteal artery is deeper and stiffer than the vein, requiring higher force to produce compression, and so the incidence of this syndrome is least likely, especially in isolation of nerve or venous symptoms. None of the reported cases of arterial occlusion mentioned venous compression.…”
Section: Discussionmentioning
confidence: 99%
“…15 Popliteal vessel compression can also cause a true thrombophlebitic 18 or pseudothrombophlebitic syndrome, 19,20 and in rare cases of arterial compression, claudication of the lower extremity can occur due to intermittent ischemia. [21][22][23][24][25] The differential diagnosis for syndromes associated with compression of the neurovascular bundle include intraneural ganglion cyst of distal divisions of the sciatic nerve, [26][27][28] adventitial cyst of the popliteal artery, thrombophlebitic syndrome caused by DVT of the lower extremity, 18,[29][30][31][32] synovial sarcoma of the knee joint, popliteal entrapment syndrome, posterior compartment syndrome of the lower leg, [33][34] popliteal artery aneurysm, and Baker cyst. A popliteal cyst may be comorbid with a number of these conditions, including communication of the cyst with an adventitial cyst of the popliteal artery, 35 development of a synovial sarcoma within the cyst, 36,37 and also rupture of the cyst, resulting in the acute development of a compartment syndrome.…”
mentioning
confidence: 99%
“…In those arteries that have been resected, the histological picture varies. In three specimens the cyst was a large sac-like cavity confined to the adventitia, with no evidence of communication between the cystic formation and the arterial lumen (Ejrup & Hiertonn, 1954;Robb, 1960). The cyst wall itself consisted of a thin layer of dense fibrous tissue lined by a single layer of flattened endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bliss and his colleagues (1963) found the suddenness of the onset of symptoms difficult to explain, and suggest that a minute intramural dissection may give rise to arterial spasm, followed by an effusion in the arterial wall, which subsequently became mucoid. Robb (1960) suggested that the cyst was formed from a piece of synovial membrane either from a nearby tendon sheath or from the knee joint, which had become attached to the artery as a result of trauma or a developmental abnormality, and the argument has the support of Lewis and his colleagues (1967). Cystic degeneration of other arteries Cystic degeneration affecting the iliofemoral arterial system has now been reported seven times (Table 3), and all the cases except one have been men.…”
Section: Discussionmentioning
confidence: 99%